The substantiation of urban habitats peer land exchange in Ukraine - Malashevskyi, Mykola; Bugaienko, Olena (Geodesy and Cartography, 2016)
Land exchanges have been used around the world and are recognized as one of the principal ways of land reallocation. At the moment, placement of facilities and socially and environmentally important objects in the existing housing is of special importance in Ukraine. There is a need for finding ways of increasing the effectiveness of such projects with the help of peer exchange. With this aim, engineering solutions for the built-up land exchange should be found. Research, provided in this paper, aims at substantiating peer land plot exchange calculation at the inhabited locality improvement. Key factors defining value of the built-up land (or the land to be built-up) have been defined. Placement and physical characteristics, which should be taken into consideration to achieve the land exchange equality, have been singled out. Based on the existing calculation of peer agricultural land exchange in Ukraine a methodology for built-up (or to be built-up) land, which considers the peculiarities of the land usage, has been proposed. Calculation of peer built-up (or that to be built-up) urban land exchange has been presented. Technical data characterizing the main influence factors in the discourse of the provided land exchange approach have been offered. The calculation algorithm on the example of peer residential housing land plot exchange in Kyiv has been provided.